2008
DOI: 10.1681/asn.2007090993
|View full text |Cite
|
Sign up to set email alerts
|

A Bimodal Association of Vitamin D Levels and Vascular Disease in Children on Dialysis

Abstract: In addition to its classical role in calcium-phosphate homeostasis, vitamin D has anti-inflammatory effects that may influence vascular disease. This study examined the impact of vitamin D levels on the vascular phenotype in 61 children who had been on dialysis for Ն3 mo and in 40 age-matched control subjects. All dialysis patients were prescribed daily oral 1-␣ hydroxyvitamin D 3 . 92% of patients were deficient in ,25(OH) 2 D] levels were low in 36% and high in 11% of patients. There was a weak correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(126 citation statements)
references
References 44 publications
(73 reference statements)
5
120
0
1
Order By: Relevance
“…In patients with CKD-5D, PWV may be increased by dosing with calcium, calcitriol, or its analogs and by phosphate exposure (30)(31)(32), although physiologic levels of 25(OH)D and 1,25(OH) 2 D may maintain stability of the vascular smooth muscle phenotype (33). In this study, baseline PWV values were directly associated with age and inversely to 25(OH)D levels.…”
Section: Pwvmentioning
confidence: 63%
“…In patients with CKD-5D, PWV may be increased by dosing with calcium, calcitriol, or its analogs and by phosphate exposure (30)(31)(32), although physiologic levels of 25(OH)D and 1,25(OH) 2 D may maintain stability of the vascular smooth muscle phenotype (33). In this study, baseline PWV values were directly associated with age and inversely to 25(OH)D levels.…”
Section: Pwvmentioning
confidence: 63%
“…In this regard, Shroff et al have recently reported a bimodal association between vascular calcification and 1,25D levels in dialyzed children, but no association between 25D levels and the vascular measurements (22). London et al observed that in adult hemodialysis patients, 1,25D and 25D levels were negatively correlated with aortic stiffness but not with vascular calcification (13).…”
Section: Discussionmentioning
confidence: 98%
“…In animal models, exogenous administration of supraphysiological doses of VDR activators has been associated with both the incidence and progression of vascular calcification (19,20), whereas the administration of VDR activators at more physiologic doses (i.e., just enough to correct secondary hyperparathyroidism) protect against aortic calcification (21). In a CKD setting, a recent study in adult hemodialysis patients described an association between 25D deficiency and arterial stiffness (13), whereas dialyzed children showed a bimodal association between 1,25D levels and vascular calcification and stiffness (22).…”
mentioning
confidence: 99%
“…If not closely supervised, prolonged high-dose supplements of vitamin D or its active derivatives may lead to hypercalcemia and hyperphosphatemia and induce adverse effects such as vascular calcification (83)(84)(85). Of interest, both vitamin D deficiency and vitamin D excess have been shown to be associated with an increased prevalence of vascular calcification (63).…”
Section: Case In Favor Of Vitamin D or Active Vitamin D Derivatives Amentioning
confidence: 99%